ESBL and MBL genes detection and plasmid profile analysis from Pseudomonas aeruginosa clinical isolates from Selayang Hospital, Malaysia - M. H. M., Nazmul; M. K. K., Fazlul; Rashid, Shah Samiur; Doustjalali, Saeid Reza; Farzana, Yasmin; Al-Jashamy, Karim; Munira, Bhuiyan; Sabet, Negar Shafiei (Lahore Medical & Dental College, 2017)
Aim: This study was carried out to detect the ESBL and MBL genes and plasmid profile analysis among the clinical isolates of Pseudomonas aeruginosa. Methods: For this study, 54 P. aeruginosa isolates were obtained from blood, skin, pus, respiratory, eyes, urine and sputum of both paediatric and adult patients from Selayang Hospital, Kuala Lumpur. Double Disk Synergy Test (DDST) and E-test were used to detect both ESBL and MBL genes. Plasmids were detected using Close and Rodriguez with modification (1982) method. QIAprep Spin Kit was also used to extract Plasmid DNA and the method was followed according to manufacturer’s instructions. Results: Among all the P. aeruginosa isolates, 12.97% were ESBL positive, but none of the isolates were found to produce MBLs. Plasmids were detected in ten isolates with the POR of (18.51%). The overall sizes of the plasmid DNA ranged from the lowest 1.8 kb to the highest 14 kb. These ten isolates appear to harbor one or more plasmids with the maximum of four plasmids. Three isolates possessed single sized plasmids (3400bp-4600bp) while three isolates had four plasmids (1800bp-5800bp) and four isolates had two plasmids (220bp-14000bp). Conclusion: This study shows the prevalence of ESBL and MBL genes and also shows the presence of plasmids among the clinical isolates of P. aeruginosa.